1982
DOI: 10.1111/j.1471-0528.1982.tb04719.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of an antihypertensive drug, labetalol, on uteroplacental blood flow

Abstract: Summary. The effect of a new antihypertensive drug, labetalol, on uteroplacental blood flow was determined in eight pre‐eclamptic women. After injection of 0.5 mCi of 113mIn the radioactivity in the placenta was recorded by a gamma camera linked to a computer and the placental blood‐flow index was calculated from the ratio between the maximum radioactivity of the isotope‐accumulation curve and the rise time of the curve. Labetalol, a combined α‐ and β‐adrenoceptor antagonist was given intravenously and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

1983
1983
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 16 publications
0
11
0
1
Order By: Relevance
“…This is consistent with previously published data using labetalol at similar doses as those administered in our study. Lunell et al [30] observed a significant reduction in BP starting from the 10th min of therapy. Michael [29] and Garden et al [28] used prospective continuous infusion doses (20-160 mg per hour in the first study and 0.5 and 3 mg/kg per hour in the second) and recorded a significant BP reduction as soon as the 5th min of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previously published data using labetalol at similar doses as those administered in our study. Lunell et al [30] observed a significant reduction in BP starting from the 10th min of therapy. Michael [29] and Garden et al [28] used prospective continuous infusion doses (20-160 mg per hour in the first study and 0.5 and 3 mg/kg per hour in the second) and recorded a significant BP reduction as soon as the 5th min of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly used in obstetrics in the treatment of preeclampsia. [11][12][13][14][15] The formulation for intravenous injection is isotonic with a pH ranging from 3 to 4. Each mL of solution contains 5 mg of labetalol hydrochloride, 45 mg of anhydrous dextrose, 0.1 mg of EDTA, 0.8 mg of methylparaben and 0.1 mg of propylparaben as preservatives.…”
Section: Discussionmentioning
confidence: 99%
“…Labetalol was administered via IV route after 30 minutes, a second uteroplacental blood flow index was calculated which showed no change. 8 Similar to…”
Section: Discussionmentioning
confidence: 99%